Métodos integrados para organização de redes de sensores sem fio com sorvedouro móvel e controle de densidade - Wagner Moro Aioffi (2007)
In this work we present two new methods for organization of Wireless Sensor Network (WSN). These methods integrate the density control and sink mobility to optimize some important WSN' metrics. In traditional methods, with multi-hop communication, the message routing process is pointed, by some authors, as the largest energy consumer. To reduce the routing energy consume, the mobile sink has been introduced in WSN enabling single-hop communication. However, the proposed methods with mobile sink shows a high message delivery delay compared to tradicional methods. To consider this problem, we propose the SHS (Single-hop strategy) method, that extends the existing methods with the objective of reducing message delivery delay. The single-hop communication constraint imposes sensor nodes to be in the sink communication range to report its data, what increases the message delivery delay. To approximate the methods with mobile sink to tradicional methods based on delivery delay performance, we propose the MHS (Multi-Hop Strategy). The MHS method extends the SHS implementing a multi-hop communication with a limited number of hops. With this strategy, the MHS reduces the time needed to collect sensor nodes data and the message delivery delay by increasing the cluster range. Both methods integrate the sink mobility and density control, where the sink is responsible to control and to deploy to the sensor nodes. The computational results show a significant performance increase in metrics such as WSN lifetime, coverage and connectivity. As expected, the proposed methods are not as efficient as the tradicional ones, regarding the delivery delay metric. However, some parameter adjustment such as sink speed, network density and number of mobile sink could increase significantly this metric performance.